Deteksi Dini Masalah Emosi dan Perilaku pada Usia 11 – 18 Tahun di SMK YPPP Wonomulyo - Susanti, Rezky; Akbar K., Fredy (Yayasan Mandar Indonesia, 2022)
Adolescents are individuals aged 11-12 years to 20-21 years. Adolescence is a period of transition where there are many changes in the individual, both physical, and psychological changes. Adolescents who are identical with high curiosity greatly affect their every behavior in everyday life because not everything they want to know is good, sometimes there are some teenagers who fall into negative things due to wrong steps. Especially when viewed from the emotional aspect of teenagers who are still unstable and cannot control themselves well. On the other hand, adolescents are also faced with the challenges of puberty, changes in social and environmental roles in order to achieve independence. These challenges have the potential to cause emotional and behavioral problems for adolescents. These emotional and behavioral problems are very common among teenagers, therefore it is necessary to detect them so that they can be prevented as early as possible. This study aims to identify emotional and behavioral problems at the age of 11-18 years at YPPP Wonomulyo Vocational High School. Research method is a type of quantitative research with data collection techniques were carried out using a strength and weakness questionnaire (SDQ) which will assess emotional and behavioral problems in adolescents. Sampling using total sampling technique and the results obtained by research with 550 respondents, the adolescent emotional and behavioral problems have a normal percentage more than the threshold/borderline percentage and abnormal percentage. So it can be concluded that the level of emotion and behavior of adolescents in YPPP Wonomulyo Vocational High School with normal emotional symptoms is 328 (60%), threshold/borderline 80 (14%), abnormal is 142 (26%) and normal behavior problems are 432 (78%), threshold 75(14%), abnormal 43(8%).